2000
DOI: 10.1152/ajpcell.2000.279.4.c1189
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P2X7 purinoceptors on human lymphocytes and monocytes: evidence for nonfunctional P2X7 receptors

Abstract: Lymphocytes from normal subjects and patients with B-chronic lymphocytic leukemia (B-CLL) show functional responses to extracellular ATP characteristic of the P2X(7) receptor (previously termed P2Z). These responses include opening of a cation-selective channel/pore that allows entry of the fluorescent dye ethidium and activation of a membrane metalloprotease that sheds the adhesion molecule L-selectin. The surface expression of P2X(7) receptors was measured in normal leucocytes, platelets, and B-CLL lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
216
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(238 citation statements)
references
References 49 publications
15
216
2
Order By: Relevance
“…However as described earlier, monocytes, in contrast to monocyte-derived macrophages, do not form pores in [46,47]. Considering the crucial role of ionic compositions of the extracellular medium in P2X 7 receptor activation by ATP [48][49][50][51], Gudipaty et al [37] showed that replacement of extracellular Na + and Cl − with K + and nonhalide anions strongly facilitated ATP-dependent pore formation in monocytes. In line with their data, we also observed that these ionic conditions resulted in an increased agonist affinity, such that 100 ÎŒM ATP was sufficient for the activation of a nonselective pore by P2X 7 receptors.…”
Section: Engagement Of P2x 4 Receptorsmentioning
confidence: 88%
“…However as described earlier, monocytes, in contrast to monocyte-derived macrophages, do not form pores in [46,47]. Considering the crucial role of ionic compositions of the extracellular medium in P2X 7 receptor activation by ATP [48][49][50][51], Gudipaty et al [37] showed that replacement of extracellular Na + and Cl − with K + and nonhalide anions strongly facilitated ATP-dependent pore formation in monocytes. In line with their data, we also observed that these ionic conditions resulted in an increased agonist affinity, such that 100 ÎŒM ATP was sufficient for the activation of a nonselective pore by P2X 7 receptors.…”
Section: Engagement Of P2x 4 Receptorsmentioning
confidence: 88%
“…Adenosine, ADP and UTP did not cause CD62L shedding, while oxidised ATP inhibited both ATP-and BzATP-induced CD62L shedding from these cells [55]. Furthermore, KN-62 inhibited ATP-induced CD62L shedding from CLL lymphocytes [34,56], while BzATP-induced CD62L shedding was impaired in CLL cells expressing non-functional P2X7 [57]. Collectively, confirming a role for P2X7 in this process.…”
Section: Cd62l (L-selectin)mentioning
confidence: 81%
“…It has been proposed that activation of neutrophils with the chemo-attractant N-formylmethionyl-leucyl-phenylalanine (fMLP) induced the appearance of purinergic responses [9,43]. Such activation could induce trafficking of purinergic receptors to plasma membrane as was suggested by Gu et al [19]. To test this hypothesis, isolated neutrophils were treated with 1 ÎŒM fMLP during 10 min at 37°C and then subjected to patch clamp to measure the ATP-activated currents.…”
Section: Resultsmentioning
confidence: 99%
“…Although mRNA for P2X 7 as well as P2X 1 and P2X 4 has been detected by some groups in human neutrophils [8,42], others failed to detect both mRNA and protein in whole human neutrophils [31,44]. Furthermore, it has been suggested that most of P2X 7 R are in the cytosol of human neutrophils serving as a reserve to be recruited to the plasma membrane after cell activation [19]. However, treatment of neutrophils with lipopolysaccharide (LPS), which is known to up-regulate P2X 7 R expression in monocytes [22], did not induce P2X 7 R protein expression [44].…”
Section: Introductionmentioning
confidence: 99%